2020
DOI: 10.1186/s40985-020-00133-6
|View full text |Cite
|
Sign up to set email alerts
|

Voting, health and interventions in healthcare settings: a scoping review

Abstract: Background: In democracies, voting is an important action through which citizens engage in the political process. Although elections are only one aspect of political engagement, voting sends a signal of support or dissent for policies that ultimately shape the social determinants of health. Social determinants subsequently influence who votes and who does not. Our objective is to examine the existing research on voting and health and on interventions to increase voter participation through healthcare organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 48 publications
3
67
0
Order By: Relevance
“…4,23 An under-representation of these voters may impact policy decisions pertaining to medical care and population health, and some studies have accordingly called for healthcare workers to address barriers to voting faced by patients. 2,7,8,[24][25][26][27] Importantly, several studies have indicated that enfranchising marginalized populations is associated with improved health outcomes, due to these voters disproportionately supporting policies focused on equity, including healthcare and education. 1,23,28 There are several ways that healthcare workers and institutions may act on this study's findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,23 An under-representation of these voters may impact policy decisions pertaining to medical care and population health, and some studies have accordingly called for healthcare workers to address barriers to voting faced by patients. 2,7,8,[24][25][26][27] Importantly, several studies have indicated that enfranchising marginalized populations is associated with improved health outcomes, due to these voters disproportionately supporting policies focused on equity, including healthcare and education. 1,23,28 There are several ways that healthcare workers and institutions may act on this study's findings.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research indicates that Americans with significant health conditions or belonging to marginalized populations are disproportionately under-represented in terms of voter turnout. [1][2][3][4][5][6] Healthcare institutions have the potential to improve democratic participation, 2,7,8 and one method to achieve this is emergency absentee voting. The emergency absentee voting process allows voters to obtain and submit an absentee ballot if they experience a medical emergency or are hospitalized after their state's regular absentee deadline, which usually falls days or weeks before election day.…”
Section: Introductionmentioning
confidence: 99%
“…So in practice, without registration they are not accepted in hospitals and polyclinics, it is difficult to identify a child in school, difficulties arise when applying for a job. In some cases, political and civil rights may also be affected such as rights to marriage, the right to inviolability in family life, the right to access justice, the right to participate in elections (Brown et al, 2020).…”
Section: Legislative Normsmentioning
confidence: 99%
“…Regarding health and voter participation, a study of 30 European countries found that health does have an effect on turnout and that this effect is largest among the elderly [9]. Similarly, a review of 17 studies examining the relationship between voting and health across the US and Europe demonstrated lower voter participation was consistently related to poor self-rated health [10]. Given its relationship to turnout, many analysts have stressed the importance of studying the correlation between health and partisanship in political science research [11].…”
Section: Introductionmentioning
confidence: 99%